Loadability Analysis of Smart Solid-State Transformer Considering its Interactions Amongst all the Ports - Junru Chen; Yi Zhang; Muyang Liu; Yutian Chen; Rongwu Zhu (IEEE Open Access Journal of Power and Energy)
Smart solid-state transformers (STs) have been proposed to modernize the distributed renewable resources dominated distribution system and facilitate the integration of different subsystems/resources as an energy hub/router. A solid power deliver amongst these integrated subsystems is critical to maintain the power balance and to ensure the ST stable operation, while the research on ST loadability analysis is insufficient. Generally, the ST is composed of three-stage offering medium voltage alternative current (MVAC), medium voltage direct current (MVDC), low voltage direct current (LVDC) and low voltage alternative current (LVAC) connectivity. Although the voltage at each port is independently controlled, the power conversion among these ports is electrically coupled and constrained by the maximum deliverable power of each stage. This paper analyzes the operating points of the ST stage by stage with respect to its loadbility and defines the stable operational region of the ST considering the interactions amongst these stages. Moreover, effects of the current limits, voltage regulation and reactive power compensation on the ST loadability and stability enhancement are considered. RT-Lab platform serves to verify the stable operation region of the ST and the efficiency of the above loadability enhancement methods.